2012
DOI: 10.1007/s11427-012-4367-y
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction and experimental verification of miRNAs in Panicum miliaceum L.

Abstract: MicroRNAs (miRNAs) are a class of non-coding RNAs that play critical roles in post-transcriptional regulation. Their target genes are involved in a variety of biological processes such as development, metabolism, and stress response. Panicum miliaceum L. (Panicum) is an important grain crop, but, until now, no miRNAs have been identified in this plant. Using a homology search based on expressed sequence tag (EST) analysis and miRNA precursor secondary structure, a total of 43 new miRNAs were identified. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…[39] Moreover, Wu and co-workers showed COMT up-regulation in pancreatic cancer cell lines and in a pancreatic cancer tissue compared to normal tissue at both transcript and protein levels. [40] A role of COMT in an estrogen-induced carcinogenesis was studied mainly in terms of its polymorphisms, where a higher risk of BC was related to Val-158-Met polymorphism in meta-analysis of Chinese population, [41] while other meta-analysis showed lower BC risk related to the same polymorphism (and lower COMT activity) specifically in Caucasian population. [42] Weisz and co-workers described COMT as an enzyme responsible for degradation of catecholestrogens, which might protect breast cells against the carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Moreover, Wu and co-workers showed COMT up-regulation in pancreatic cancer cell lines and in a pancreatic cancer tissue compared to normal tissue at both transcript and protein levels. [40] A role of COMT in an estrogen-induced carcinogenesis was studied mainly in terms of its polymorphisms, where a higher risk of BC was related to Val-158-Met polymorphism in meta-analysis of Chinese population, [41] while other meta-analysis showed lower BC risk related to the same polymorphism (and lower COMT activity) specifically in Caucasian population. [42] Weisz and co-workers described COMT as an enzyme responsible for degradation of catecholestrogens, which might protect breast cells against the carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2012) have done preliminary work in characterizing proso millet microRNAs (miRNAs), which are non-coding RNAs important in post-transciptional regulation. Since there are limited proso millet genome sequences, Wu et al (2012) used ESTs to predict miRNAs instead of using genomic survey sequence analysis as has been done in other crops.…”
Section: Genetics and Genomics Of Proso Milletmentioning
confidence: 99%
“…Since there are limited proso millet genome sequences, Wu et al (2012) used ESTs to predict miRNAs instead of using genomic survey sequence analysis as has been done in other crops. Wu et al (2012) identified 43 potential miRNAs and their gene targets involved in biological processes such as development, metabolism and stress response. They selected 12 miRNAs to validate and eight were verified by Northern blot hybridizations.…”
Section: Genetics and Genomics Of Proso Milletmentioning
confidence: 99%
“…In the latter study, a hybrid genotype outperformed local varieties, validating the potential in breeding highly WUE proso millet. Preliminary work in characterizing proso miRNAs has been accomplished with the goal of understanding mechanisms responsible for the cereal's impressive drought resistance (Wu et al, 2012 ). Despite its drought tolerance, proso is best adapted to temperate latitudes unlike other small millets.…”
Section: Diversity Of the Small Milletsmentioning
confidence: 99%